Post-COVID-19 syndrome in patients with primary Sjögren's syndrome after acute SARS-CoV-2 infection - (:unkn) unknown (My University, 2021)
OBJECTIVES: To analyse the frequency and characteristics of post-COVID-19 syndrome in patients with primary Sjögren's syndrome (pSS) affected by acute SARS-CoV-2 infection. METHODS: By the first week of April 2021, all centres included in the Big Data Sjögren Consortium were contacted asking for patients included in the Registry diagnosed with SARSCoV-2 infection according to the ECDC guidelines. According to the NICE definitions, symptoms related to COVID-19 were classified as acute COVID-19 (signs and symptoms for up to 4 weeks), ongoing symptomatic COVID-19 (presence of signs and symptoms from 4 to 12 weeks) and post-COVID-19 syndrome (signs and symptoms that continue for > 12 weeks not explained by an alternative diagnosis after a protocolized study). RESULTS: We identified 132 patients who were followed a mean follow-up of 137.8 days (ranging from 5 days to 388 days) after being diagnosed with COVID-19. In the last visit, 75 (57%) patients remained symptomatic: 68 (52%) remained symptomatic for more than 4 weeks fulfilling the NICE definition for ongoing symptomatic post-COVID-19, and 38 (29%) remained symptomatic for more than 12 weeks fulfilling the definition of post-COVID-19 syndrome. More than 40% of pSS patients reported the persistence of four symptoms or more, including anxiety/depression (59%), arthralgias (56%), sleep disorder (44%), fatigue (40%), anosmia (34%) and myalgias (32%). Age-sex adjusted multivariate analysis identified raised LDH levels (OR 10.36), raised CRP levels (OR 7.33), use of hydroxychloroquine (OR 3.51) and antiviral agents (OR 3.38), hospital admission (OR 8.29), mean length of hospital admission (OR 1.1) and requirement of supplemental oxygen (OR 6.94) as factors associated with a higher risk of developing post-COVID-19 syndrome. A sensitivity analysis including hospital admission in the adjusted model confirmed raised CRP levels (OR 8.6, 95% CI 1.33-104.44) and use of hydroxychloroquine (OR 2.52, 95% CI 1.00-6.47) as the key independent factors associated with an enhanced risk of developing post-COVID-19 syndrome. CONCLUSIONS: This is the first study that analyses the frequency and characteristics of post-COVID-19 syndrome in patients affected by a systemic autoimmune disease. We found that 57% of patients with pSS affected by COVID-19 remain symptomatic after a mean follow-up of 5 months. The risk of developing post-COVID-19 syndrome in patients who required hospitalisation was 8-times higher than in non-hospitalised patients, with baseline raised CRP levels and the use of hydroxychloroquine being independent risk factors for post-COVID-19.
Keywords: Humans; COVID-19; SARS-CoV-2; Fatigue; Sjogren's Syndrome